Côte d'Ivoire : Investment Climate Survey Report - World Bank (Washington, DC, 2013)
This Investment Climate Survey Report (ICSR) for Cote d'Ivoire evaluates the country's business environment by (i) analyzing barriers to private sector investment and growth and how they vary among different types of firms, (ii) benchmarking the Ivorian investment climate and firm performance to that of other countries and (iii) providing recommendations to promote and strengthen the private sector. The ICSR is supported by the statistical analysis of a survey of firms based in Cote d'Ivoire's major urban centers, as well as data from other sources. This ICSR identifies key areas where investment climate reforms may be warranted. It is largely based on the analysis of Enterprise Survey data; which are surveys of mostly manufacturing, formal sector enterprises in the major industrial centers of an economy. Cote d'Ivoire is one of the very few countries in Sub-Saharan Africa with a ratio of manufacturing to GDP higher than 15 percent.